Molecular epidemiology driving precision medicine: Unraveling some genetic and environmental determinants in certain Colombian populations (2024)
The interplay between molecular epidemiology and precision medicine, coupled with collaborative initiatives may drive Colombia into a new era of healthcare tailored to the individualized genetic profile in the Colombian population. Studying chronic diseases such as Neuromyelitis Optica spectrum disease (NMOSD), chronic kidney disease (CKD), hemophilia A (HA) and B (HB), and von Willebrand disease (VWD) in Colombia is crucial to better understand their prevalence, presentation patterns, and treatment needs in the population. This enables the development of effective prevention, diagnostic, and medical care strategies tailored to the country's specific needs. Increased attention to diversity will increase the accuracy, utility, and acceptability of using this genomic information for clinical care (6). Considering this context, where chronic diseases pose significant health challenges, ME approaches through affordable genetic and bioinformatic research has been applied in this thesis work to address these issues. Three different studies exemplify this integration. The first chapter, divided into two sections, will focus on, first the characterization of HLA class II alleles in NMOSD patients in Colombia, and second, identifying new NMOSD disease biomarkers as well as understanding the studied population structure. The second chapter will focus on understanding the impact of genetic polymorphisms on mercury levels and CKD, and the third chapter will focus on identifying the genetic mutations associated with inherited bleeding disorders in Colombia and developing and implementing low-cost genetic diagnostic methods. Given that Colombia may present one of the highest prevalence rates of NMOSD in Latin America (14), we highlighted the need for further investigation into the contributing factors of this disease. In this sense, understanding the specific HLA class II genetic landscape in our population can provide valuable insights into the complex interplay between genetic predisposition and environmental factors influencing NMOSD susceptibility. Our first study represents the first exploration of HLA patterns in NMOSD patients in Colombia and, to our knowledge, has one of the largest HLA characterized NMOSD cohorts studied in Latin America. The inclusion of multidimensional genetic biomarker data from large numbers of subjects exemplifies the consideration of human genomics within precision public health research (15). In addition to these genomic biomarkers, the ability to detect other biomarkers including the transcriptome is also increasing significantly. This is also considered in Chapter 1, where FOXP3 gene expression was measured and compared to healthy controls as a possible new biomarker of the disease. The second chapter presents a study placed in the field of environmental health. The integration of human genomic research within environmental health research may help to elucidate how individual-level factors (e.g., genetic data) and macro-level factors interact to influence health, providing a better understanding of mechanisms underlying complex gene-environment interactions (15). In Colombia, where environmental exposures may vary across regions, understanding how these factors interact with genetic predispositions becomes crucial. The study on the impact of genetic polymorphisms on mercury (Hg) levels and CKD sheds light on the intricate relationship between genetic variations, environmental exposures, and disease outcomes in the Colombian population. Ultimately, the investigation into inherited bleeding disorders in Bogotá incorporated genetic and bioinformatic methods to enhance the precision of diagnoses. This not only refines the detection of individuals with specific genetic conditions but also streamlines the creation of personalized treatment plans based on the individual's genetic background. Consequently, these findings play a crucial role in comprehending the economic and health implications of precision public health initiatives, particularly regarding their support for health equity. With improved data, healthcare resources can be better managed and allocated (15). In conclusion, this thesis represents an effort to delve into the molecular etiology of some chronic human diseases, from autoimmune disorders to metabolic and genetic conditions. This effort provided valuable insights that can guide the development of more effective diagnostic approaches in the clinical setting and in the development of biomarkers that can support the public health fields of both early diagnosis and intervention to limit the burden of these diseases.